The archaeological survey of Sudanese Nubia 1963-69 : the pharaonic sites - Edwards, David N., (Sudan Archaeological Research Society publication ;, 2020)
This volume, focusing on pharaonic sites, brings to publication the records of the Archaeological Survey of Sudanese Nubia (ASSN). These records represent a major body of data relating to a region largely now lost to flooding and of considerable importance for understanding the archaeology and history of Nubia.